Neuroprotective effects of pyrroloquinoline quinone against rotenone injury in primary cultured midbrain neurons and in a rat model of Parkinson's disease. (September 2016) - Zhang, Qi; Chen, Shuhua; Yu, Shu; Qin, Jiaojiao; Zhang, Jingjing; Cheng, Qiong; Ke, Kaifu; Ding, Fei
Abstract: Mitochondrial dysfunction and oxidative stress have been implicated in the pathogenesis of Parkinson's disease (PD). Pyrroloquinoline quinone (PQQ), a redox cofactor in the mitochondrial respiratory chain, has been reported to protect SH-SY5Y cells from cytotoxicity induced by rotenone, a mitochondrial complex I inhibitor. In this study, we aimed to investigate the neuroprotective effects of PQQ against rotenone injury in primary cultured midbrain neurons and in a rat model of Parkinson's disease. Pre-treatment with PQQ prevented cultured midbrain neurons from rotenone-induced apoptosis, restored mitochondrial membrane potential, inhibited intracellular reactive oxygen species (ROS) production, and affected microtubule depolymerization. On the other hand, intraperitoneal administration of PQQ exerted protective effects on rats that had received rotenone injection into the medial forebrain bundle through decreasing the apomorphine-evoked rotation, inhibiting neuronal loss and TH down-regulation in SNc, increasing the antioxidative ability, and regulating intracellular expressions of Ndufs1 and Ndufs 4. Silencing of Ndufs1 or Ndufs4 in cultured SH-SY5Y cells or midbrain neurons reduced the neuroprotective effects of PQQ. Overall, our results suggest that PQQ neuroprotection may be mediated by the inhibition of mitochondrial dysfunction and oxidative stress as well as by the gene modulation of Ndufs1 and Ndufs4. Highlights: PQQ ameliorated rotenone-induced neuronal damage both in vitro and in vivo . PQQ reduced oxidative stress and improved mitochondrial functions in PD models. PQQ regulated microtubule depolymerization in rotenone injured neurons. Neuroprotection of PQQ might be mediated by modulation of Ndufs1 and Ndufs4.